Two Decades of Microlearning in Education: A Bibliometric Exploration - Dewi, Fitrika Kumala; Irfan, Dedy; Effendi, Hansi; Mulya, Rudi; Dicky Putra, Metria; Mulia, Denal (Universitas Pendidikan Ganesha, 2025)
Microlearning has shown positive effects, but there is still a lack of specific mapping of this topic. This creates an empirical gap that requires a scientific procedure to overcome it. Therefore, a bibliometric analysis was conducted that reviewed several previous publications related to microlearning in education, especially over the past twenty years, to fill this gap. Through a specific search, there were 127 documents published from 2005-2024 sourced from Scopus metadata. The data obtained were analyzed using Biblioshiny, R Studio, and VOSviewer software. The results of the analysis show that microlearning continues to grow from year to year; a significant increase occurred in 2020, which indicates the application of this method due to the COVID-19 pandemic. In addition, the country that publishes the most microlearning in education is China. Then, through keyword analysis, microlearning is closely related to technology platforms and systems in learning. The findings produced through this paper are expected to be used as a reference for readers who want to directly find publication trends on this topic without having to read relevant articles one by one. In conclusion, interest in microlearning continues to increase, with significant contributions from various countries and institutions. The implication is that this study reveals the trends, developments, and directions of microlearning research in the last two decades, which can be a strategic basis for curriculum development and educational innovation in the future.